Cell type-specific chromatin immunoprecipitation from multicellular complex samples using BiTS-ChIP - Bonn, Stefan; Gavin, Anne-Claude (Nature protocols, 2012)
This protocol describes the batch isolation of tissue-specific chromatin for immunoprecipitation (BiTS-ChIP) for analysis of histone modifications, transcription factor binding, or polymerase occupancy within the context of a multicellular organism or tissue. Embryos expressing a cell type-specific nuclear marker are formaldehyde cross-linked and then subjected to dissociation. Fixed nuclei are isolated and sorted using FACS on the basis of the cell type-specific nuclear marker. Tissue-specific chromatin is extracted, sheared by sonication and used for ChIP-seq or other analyses. The key advantages of this method are the covalent cross-linking before embryo dissociation, which preserves the transcriptional context, and the use of FACS of nuclei, yielding very high purity. The protocol has been optimized for Drosophila, but with minor modifications should be applicable to any model system. The full protocol, including sorting, immunoprecipitation and generation of sequencing libraries, can be completed within 5 d.